2022
DOI: 10.17645/pag.v10i4.5798
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19‐Related Conspiracy Myths, Beliefs, and Democracy‐Endangering Consequences

Abstract: Since late 2020, protests against government measures to contain the Covid‐19 pandemic have swept across Germany. At the forefront of these protests was the Querdenker Movement, a heterogeneous alliance of ordinary citizens, hippies, esotericists, opponents of conventional medicine, Christian fundamentalists, and right‐wing extremists bonded by their shared belief in conspiracy myths. This contribution draws upon the theoretical framework of the studies on the authoritarian personality to dissect the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In the context of the COVID-19 pandemic, overarching epistemic mistrust also represents a key factor contributing to the increased prevalence of conspiracy beliefs (Magarini et al ., 2021 ). Specific examples of such associations include the correlation between conspiracy mentality and mistrust in scientific institutions and health organizations, resulting in reduced compliance with preventive guidelines (Plohl & Musil, 2021 ); mistrust in democratic political institutions and non-populist governments (Martinez et al ., 2022 ; Pickel et al ., 2022 ); and mistrust in conventional media platforms and news outlets, particularly when coupled with increased social media use (van der Linden et al ., 2020). These correlations between mistrust in various societal authorities responsible for information dissemination and conspiracy beliefs have been corroborated in multinational, representative samples (De Coninck et al ., 2021 ) and concerning both general and specific COVID-related CTs (Freeman et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the COVID-19 pandemic, overarching epistemic mistrust also represents a key factor contributing to the increased prevalence of conspiracy beliefs (Magarini et al ., 2021 ). Specific examples of such associations include the correlation between conspiracy mentality and mistrust in scientific institutions and health organizations, resulting in reduced compliance with preventive guidelines (Plohl & Musil, 2021 ); mistrust in democratic political institutions and non-populist governments (Martinez et al ., 2022 ; Pickel et al ., 2022 ); and mistrust in conventional media platforms and news outlets, particularly when coupled with increased social media use (van der Linden et al ., 2020). These correlations between mistrust in various societal authorities responsible for information dissemination and conspiracy beliefs have been corroborated in multinational, representative samples (De Coninck et al ., 2021 ) and concerning both general and specific COVID-related CTs (Freeman et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this approach, several studies have found that individuals with strong conspiracy beliefs tend to interpret nonsensical statements as profound and are more likely to believe in the existence of supernatural phenomena ( e.g ., reincarnation, astrology) (van Prooijen et al ., 2022 ). For instance, in a representative survey in Germany, the emergence of a COVID-19-related conspiracy mentality was associated with greater beliefs in superstition and esotericism, even after controlling for other influencing factors (Pickel et al ., 2022 ). Additionally, individuals with a pronounced conspiracy mentality are more likely to ascribe credibility to distorted news from right-wing platforms compared to reliable information from mainstream newspapers (Frischlich et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The QAnon conspiracy theory reboots antisemitic blood libels, with claims that "global elites" sacrifice children in bizarre subterranean rituals (Amarasingam and Argentino, 2020). Theories of the COVID-19 vaccine's sinister origins and purposes (Pickel et al, 2022) echo both the "Doctor's Plot" conspiracy (Brandenberger, 2005) in a populist register and mid-century claims that Jews are responsible for water fluoridation and its falsely purported pacifying effects (McNeiil, 1962). More bizarre conspiracies theorize an extradimensional origin to the Jewish people, suggesting that they are reptilian aliens feeding off the negative energy of humankind (Jersusalem Post, 2023).…”
Section: Cabal: Examining Antisemitic Conspiracy Theories Of Controlmentioning
confidence: 99%
“…Against the concept of authoritarian personality (Adorno et al, 1950), Pickel et al (2022) discuss the Covid-19 pandemic as a situation leading to an increased susceptibility to conspiracy myths. Proceeding from a theory-based correlation between superstition, esotericism, and belief in conspiracy myths, they show that a conspiracy mentality is one of the key components of authoritarian character dispositions, with significant effects on anti-semitic resentment, hostility toward outgroups, the formation of anti-democratic orientations, and an increased propensity to violence.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Without overestimating conspiracy mentality as a genuinely or exclusively religious phenomenon itself, our thematic issue proves that (a particular kind of) religiosity is indeed a very relevant factor that can massively favour belief in conspiracy theories under certain circumstances but can also prevent it under alternative conditions. Although Pickel et al (2022) strictly refute the objection that adherents of conspiracy myths could be characterized as authentic democrats who are merely dissatisfied with the current state of democracy, Hidalgo's (2022) article suggests, at least theoretically, that such a position becomes available beyond a liberal conception of democracy and by starting from a concept of radical democracy. In this respect, a too simple equation that associates (the political accommodation of) religion with democracy and conspiracy belief exclusively with authoritarian political ideas does not add up.…”
Section: Overview Of Contributionsmentioning
confidence: 99%